Emotional conflict processing in adolescent chronic fatigue syndrome: A pilot study using functional magnetic resonance imaging. Issue 4 (21st April 2017) - Wortinger, Laura Anne; Endestad, Tor; Melinder, Annika Maria D; Øie, Merete Glenne; Sulheim, Dag; Fagermoen, Even; Wyller, Vegard Bruun
ABSTRACT: Introduction : Studies of neurocognition suggest that abnormalities in cognitive control contribute to the pathophysiology of chronic fatigue syndrome (CFS) in adolescents, yet these abnormalities remain poorly understood at the neurobiological level. Reports indicate that adolescents with CFS are significantly impaired in conflict processing, a primary element of cognitive control. Method : In this study, we examine whether emotional conflict processing is altered on behavioral and neural levels in adolescents with CFS and a healthy comparison group. Fifteen adolescent patients with CFS and 24 healthy adolescent participants underwent functional magnetic resonance imaging (fMRI) while performing an emotional conflict task that involved categorizing facial affect while ignoring overlaid affect labeled words. Results : Adolescent CFS patients were less able to engage the left amygdala and left midposterior insula (mpINS) in response to conflict than the healthy comparison group. An association between accuracy interference and conflict-related reactivity in the amygdala was observed in CFS patients. A relationship between response time interference and conflict-related reactivity in the mpINS was also reported. Neural responses in the amygdala and mpINS were specific to fatigue severity. Conclusions : These data demonstrate that adolescent CFS patients displayed deficits in emotional conflict processing. Our results suggest abnormalities in affective and cognitive functioning of the salience network, which might underlie the pathophysiology of adolescent CFS.